Digital-Based Tourism Village Management with The Concept of Green Economy and Harmonization as Tourism Forces - I Gusti Ayu Purnamawati; Ni Ketut Sari Adnyani (Jurnal Manajemen Perhotelan, 2024)
Digital Village is a program concept that implements government service systems, community services, and community empowerment based on information technology. Blimbingsari is a Tourism Village where the management of tourism is community-based. The type of research used in this research is qualitative research. This study aimed to determine the management of digital-based tourism villages with the concept of green economy in increasing the tourist attraction of Blimbingsari village. Blimbingsari Tourism Village also has its website, which anyone can access anywhere. On the website, the profile of Blimbingsari Village is listed, followed by what tourist attractions are offered and many more things we can access. From several aspects related to the implementation of the green economy, several things have not been able to be implemented by the Blimbingsari Tourism Village to uphold the concept of the Green Economy and harmonization. It needs further attention from related parties so that all these aspects can be fulfilled, and Blimbingsari Tourism Village can fully become a digital-based tourism village with a green economy concept, attract more tourists, and harmonize as a tourism force.